1996
DOI: 10.1002/qj.49712253605
|View full text |Cite
|
Sign up to set email alerts
|

A parametrization of the ice water content observed in frontal and convective clouds

Abstract: The properties of the ice phase in a number of cloud types are investigated to improve the ice phase parametrization in atmospheric global-climate models. Frontal clouds over southern England and the sea areas around the British Isles, maritime convective clouds over the North Atlantic, and continental convective clouds over New Mexico and Montana in the USA are studied.Ice concentrations are seen to be several orders of magnitude higher than those which could be attributed to primary nucleation of ice nuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 48 publications
5
43
0
Order By: Relevance
“…In the tropics, high skin temperature tends to trigger tropical deep convection easily. Bower et al (1996) found that the vigorous in-cloud updrafts in convective clouds do not leave enough time for supercooled droplets to transform into ice crystals, thus suppressing ice formation or pushing supercooled liquid water to a colder cloud top height. West et al (2014) concluded that the sub-grid vertical velocity enhancing leads to an increase of the liquid water path.…”
Section: Temporal Correlations Between Scfs and Meteorological Paramementioning
confidence: 99%
“…In the tropics, high skin temperature tends to trigger tropical deep convection easily. Bower et al (1996) found that the vigorous in-cloud updrafts in convective clouds do not leave enough time for supercooled droplets to transform into ice crystals, thus suppressing ice formation or pushing supercooled liquid water to a colder cloud top height. West et al (2014) concluded that the sub-grid vertical velocity enhancing leads to an increase of the liquid water path.…”
Section: Temporal Correlations Between Scfs and Meteorological Paramementioning
confidence: 99%
“…The authors note that in regions of high liquid water content, the ice particle concentration may increase by a factor of 10 on the time scale of a few minutes. In a synthesis of data from frontal clouds, maritime convective clouds, and continental convective clouds, Bower et al (1996) concluded that in most instances, ice concentrations could be reconciled with either primary production or the Hallett-Mossop riming-splintering mechanism. The authors noted that in some cases, ice was found in concentrations greater than could be explained by primary nucleation, and at temperatures outside the range applicable for riming-splintering.…”
Section: Secondary Productionmentioning
confidence: 99%
“…Table 1 in Mossop, 1978), however, this may be subject to shattering artefacts (McFarquhar et al, 2007). A common explanation is that secondary ice production by the HallettMossop process (HM) produces large numbers of additional ice particles Mossop et al, 1972;Blyth and Latham, 1993;Bower et al, 1996;Hogan et al, 2002;Huang et al, 2009;Crosier et al, 2011). This process occurs during riming at slightly supercooled temperatures (−3 • C to −8 • C) by rime splintering (Hallett and Mossop, 1974).…”
mentioning
confidence: 99%